Atipikus foglalkoztatási formák Magyarországon a kilencvenes és a kétezres években - Ágnes Hárs (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2012)
– Atypical employment is a term to describe the type of employment that is different in one or more or even in all aspects from regular employment. These types of employment promise the renewal of the labour markets. The paper discusses the penetration and structure of atypical employment during the two decades of the transition. We look at the segments in which these forms are relevant and concentrated. The time series follow the structure of atypical employment until 2010. The paper presents descriptive analysis on changes in demographic structure of atypical employment, the differences across branches and regions. Logitmodels estimate the chance of atypical employment using demographic variables, region, branches and some other indicators on the social and welfare situation.
Keywords: J21; J40; J80; 330; labour market; atypical employment; employment growth; Atypische Beschäftigung; Logit-Modell; Ungarn